Common National High School Curriculum Base and the (re)introduction of Pedagogy of Competencies: Systematic Review (Olhar de Professor, 2023)
The research aims to analyze theses and dissertations published in the Digital Library of Theses and Dissertations - BDTD, produced in the period between 2018-2021 that thematize the pedagogy of competences present in the National Common Curricular Base of High School - BNCCEM (BRAZIL , 2018). Based on the Historical-Critical theory of education, the results obtained reveal that, of 944 productions, only 10 met the criteria of the proposed investigation. The scarcity of research that addresses the influences of curriculum reform on the development of the human psyche in the light of the Historical-Critical theory; fragmented analysis of the curriculum; and the minimal understanding of education as an intentional activity in the processes of transmission and assimilation of human objectifications, constitute the gaps that justify the relevance and need for the production of knowledge on the topic portrayed in the field of Research in Education.
Keywords: High School BNCC. Pedagogy of competences. Historical-Critical theory.